A population‐based comparison of second primary cancers in Germany and Sweden between 1997 and 2006: clinical implications and etiologic aspects. (27th August 2013) - Liu, Hao; Hemminki, Kari; Sundquist, Jan; Holleczek, Bernd; Katalinic, Alexander; Emrich, Katharina; Jansen, Lina; Brenner, Hermann; ,
Abstract: Second primary cancer (SPC) has become an increasing concern in cancer survivorship. Patterns of SPCs in different populations may offer clinical implications and research priorities into SPCs. This study is devoted to compare the occurrences and rank correlations of SPCs between Germany and Sweden. Patients diagnosed with 10 common first primaries between 1997 and 2006 from the Swedish Family‐Cancer Database and 10 German cancer registries were included in this population‐based study. Spearman's rank correlation coefficients were used to evaluate the strength of the relationship of SPCs between the German and Swedish datasets. Spearman's rank correlation coefficients suggested a strong positive correlation between the German and Swedish datasets based on the ranks of thirty possible SPCs after all selected first cancers. This was also true when we compared the rankings and proportions of the five most common SPCs after site‐specific first primaries between the two populations. For kidney cancer, non‐Hodgkin's lymphoma, and leukemia the components of the five most common SPCs was exactly the same. Also, the ranking and the proportions for the three most common SPCs (i.e., colorectal, bladder, and lung cancers) after prostate cancer were identical in the two populations, as were those after most other primary cancers. The strikingly consistent patterns of SPCs in the two populations provide excellent opportunities for joint studies and they also suggest that many underlying reasons for SPC may have universal and tangible causes that await mechanistic dissection. Abstract : The strikingly consistent patterns of second primary cancers (SPCs) in German and Swedish populations provide excellent opportunities for joint studies and they also suggest that many underlying reasons for SPC may have universal and tangible causes that await mechanistic dissection.